A fast reaction-based port vulnerability assessment: Case of Tianjin Port explosion. (October 2019) - Cao, Xinhu; Lam, Jasmine Siu Lee
Abstract: There has been a growing international attention on port catastrophes after the 2015 Tianjin Port explosion, which calls for a realistic yet effective method to assess seaports' vulnerability. However, quantitative vulnerability analysis of ports during the initial post-disaster stage by traditional methods reveals challenges due to the scarcity of data and the inoperability in treating diverse data formations in a utility vulnerability inference mechanism. Thus, this study proposes a fast reaction-based port vulnerability assessment framework (FRPVA) which allows the quantification of ex-post port vulnerability. The fuzzy evidential reasoning (ER) approach and the fuzzy Technique for Order Preference by Similarity Ideal Solution (TOPSIS) are embedded in the proposed framework. The FRPVA framework is applied to the case of the 2015 Tianjin Port explosion in two assessment periods – one day and four months after the explosion. Our results show that (1) the collection and distribution system as well as the storage system are bottlenecks of the Tianjin Port; (2) the storage system is the most vulnerable among the four assessment units in both assessment periods; (3) after four months' recovery, the vulnerability condition of the loading and unloading system improves the most comparing to other three assessment units. Outputs of this framework can be useful references for various port stakeholders in prioritizing protected targets, planning routes, as well as for (re)insurance companies as a part of the catastrophe modeling.